Academic Stress among Undergraduate Nursing and Midwifery Students of a Public University - Pandey, Apsara; Dhungel, Rejina (Journal of Nursing and Health Sciences Nepal, 2024)
Background: Stress is a major contributing factor to many psychological illnesses that plague today’s society. A student’s life is impacted by a variety of stressors, including academic pressure with the expectation of success, fear of anticipated academic failure, and an uncertain future. The objective of the study was to determine the level of academic stress among undergraduate nursing and midwifery students.Methods: A descriptive cross-sectional study was conducted among 157 undergraduate nursing and midwifery students at Tribhuvan University (TU) in Kathmandu, Nepal. Different years of various bachelor level programs were taken as strata and proportionate stratified probability sampling technique was used to select the required sample for the study. The instrument included sociodemographic and academic characterization questions, as well as a self-administered, structured Scale for Assessing Academic Stress (SAAS) to collect data. Frequencies, percentages, means, standard deviations, and Pearson’s chi-square or Fishers exact test were used to analyze the data.Results: The mean age of the students was 23.08 years, with 98.7% being female and 85.4% unmarried. More than half (63.7%) of the students reported low academic stress, while 36.3% reported high academic stress. The study also revealed that stress related to cognitive indicators was higher (mean ± SD = 3.17 ± 1.91) compared to affective indicators, (mean ± SD = 1.43 ± 1.49). Academic stress among students was found to be significantly associated with their age (p = 0.004) and academic year (p = 0.026).Conclusions: Nursing and midwifery students experience academic stress, which is associated with age and academic year. Stress reduction activities such as meditation, yoga, and other recreational activities might be helpful to the students.